Pengembangan Buku Ajar Berbasis Deep Learning pada Materi Bioteknologi Untuk Meningkatkan Kemampuan Berpikir Kritis Siswa SMP: Developing a Deep Learning-Based Textbook on Biotechnology to Improve Junior High School Students' Critical Thinking Skills - Revi Ruth Susanty; Melva Silitonga; Herbet Sipahutar (Madrasah Tsanawiyah DDI Cilellang, 2026)
The development of students’ critical thinking skills remains a challenge in science learning, particularly in biotechnology topics that require conceptual understanding and higher-order thinking. This study aimed to develop a biotechnology textbook based on deep learning pedagogy to improve junior high school students’ critical thinking skills. The study employed a Research and Development (R&D) approach using the 4D model, consisting of define, design, develop, and disseminate stages. The research involved material experts, instructional design experts, layout experts, language experts, science teachers, and seventh-grade students. Data were collected through validation sheets, questionnaires, and critical thinking tests based on higher-order thinking skills (HOTS) at the cognitive levels of C4 (analyzing), C5 (evaluating), and C6 (creating). The findings indicated that the developed textbook met the criteria of validity, practicality, and effectiveness. Expert validation results showed very good qualifications, while teacher and student responses indicated excellent practicality. Furthermore, the textbook significantly improved students’ critical thinking skills, as reflected in the higher posttest scores and N-gain results in the experimental class. The findings imply that a deep learning-based textbook can support meaningful science learning and strengthen critical thinking skills in the implementation of the Merdeka Curriculum.